1977
DOI: 10.1177/00220345770560072001
|View full text |Cite
|
Sign up to set email alerts
|

An Autoradiographic Study of the Sensory Innervation of Teeth. II. Dental Pulp Periodontium

Abstract: Autoradiography of axoplasmically transported proteins revealed that both dental pulp and periodontium receive sensory innervation from the trigeminal ganglion in the form of plexuses and free and organized sensory receptors, including apparent corpuscular ones. Corpuscular receptors in the pulp suggest this tissue may be responsive to modalities other than pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…We have found that the sensory innervation of adult dog teeth is similar to that reported earlier for rat molars (Fink et al, 1975;Byers and Kish, 1976;Pimenidis and Hinds, 1977), cat teeth (Byers and Matthews, 1981), and monkey teeth (Byers and Dong, 1983). Most of the sensory axons arborize in the coronal pulp, and numerous nerve terminals are found in its peripheral plexus and extending into inner dentin.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have found that the sensory innervation of adult dog teeth is similar to that reported earlier for rat molars (Fink et al, 1975;Byers and Kish, 1976;Pimenidis and Hinds, 1977), cat teeth (Byers and Matthews, 1981), and monkey teeth (Byers and Dong, 1983). Most of the sensory axons arborize in the coronal pulp, and numerous nerve terminals are found in its peripheral plexus and extending into inner dentin.…”
Section: Discussionsupporting
confidence: 85%
“…The location of sensory receptors has also been studied extensively since the mid-1960s in human, cat, and rodent teeth, with much information derived from light and electron microscopy @ ' earnhead, 1963;Frank, 1968;Arwill et al, 1973;Corpron and Avery, 1973; Dahl and Mjor, 1973;Lilja, 1979; Byers et al, 1982) and axonal transport labeling (Fink et al, 1975;Byers and Kish, 1976; Pimenidis and Hinds, 1977; Byers, 1977Byers, , 1980Byers, , 1984Byers, ,1985; Byers and Matthews, 1981; Byers and Dong, 1983; Marfurt and Turner, 1983). Sensory fibers have been found to innervate peripheral pulp and to extend as far as 0.1-0.2 mm into dentinal tubules.…”
mentioning
confidence: 99%
“…22 In the root dentin and cementum, however, newlyformed collagen is apparently labeled, perhaps by release of H3-proline from nerve terminals and possibly reflecting a neurotropic relationship. Such a neurotropic relationship would be consistent with the findings of Stopakoff and Stiefe148 who have reported that sensory denervation affects the calcification process of dog's dentin.…”
Section: Resultsmentioning
confidence: 99%
“…For rodent lower incisor, it is innervated by sensory nerve fibres which come from IAN, sympathetic postganglionic fibres which origin from SCG and a few parasympathetic nerve fibres which are still under controversial 25 . The sensory nerve primarily governs the sense of pain, the pressure and vasodilatation regulation, 4,27 while the sympathetic nerve tends to regulate vasoconstriction functions 5,28 . Though it has been reported IANx leads to slower incisor eruption and tooth discoloration, 23 whether sympathetic nerve participate in incisor growth remains unclear.…”
Section: Discussionmentioning
confidence: 99%